Gagaan X'usyee: below the foot of the sun - Twitchell, X'unei Lance, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2024)
Identity and understanding are fluid and plural, yet the histories of violence and oppression influence and shape everything in the world because the past, present, and future exist in the same plane and at the same time. Gagaan X'usyee / Below the Foot of the Sun is a unique collection of Indigenous cultural work and Lingít literature in the tradition of Nora Marks Dauenhauer and in the broader contemporary company of Joy Harjo and Sherwin Bitsui. Focused on the history of place and the Lingít and Haida people, who recognize little separation between life and art, these forty-six poems reach into the knowledge of the past, incorporate visions currently received, and draw a path for future generations. The collection is divided into four sections based on how the Lingít talk about gagaan—the sun. Featuring some poems in English, some in Lingít, and some that combine the beauty of the two, Gagaan X'usyee / Below the Foot of the Sun displays an equal dignity in both languages that transcends monolingual constrictions.--Provided by publisher.
Keywords: American poetry -- 21st century